Who is Credit Constrained in the U. S. Economy? - Jappelli, Tullio (Quarterly Journal of Economics, 1990)
Journal Article Who is Credit Constrained in the U. S. Economy? Get access Tullio Jappelli Tullio Jappelli Istituto di Studi Economici, I.U.N., Naples, Italy Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 1, February 1990, Pages 219–234, https://doi.org/10.2307/2937826 Published: 01 February 1990